A Study about Foreign Direct Investments to Colombo Stock Market: Determinants and Impact - A Review of methodological Approaches - Kumara, V.R.I. (NSBM Green University, 2022)
The paper indicates the research findings of a systematic literature review (SLR) of key factors about Foreign Direct Investments to Colombo Stock Market: Determinants and Impact. The paper considers 22 journals over a 15-year period from year 2009 to year 2022. The SLR focuses on the key issues faced by the foreign investors and the methodological approaches critically explore the type of methodological approaches needed in future scholarship to overcome the prevailing operational bottlenecks and macro level key issues. Findings emphasis on areas needs high priority increase the foreign investors’ confidence and the studies focus on comparison other regional equity capital market development comparisons. Colombo stock exchange can be considered as the only stock exchange in Sri Lanka where all the listed companies of Sri Lanka get traded on both all share index (ASI) and S&P 20. The study will examine and emphasis the key factors affecting and influencing foreign direct investments decisions to Colombo Stock Exchange.